Influence of density on bending resistance of wooden beams under fire situation and proposal of a new equation - Perini, Pedro Verona; Bolina, Fabrício Longhi (Seven Editora, 2024)
Targeting to identify the correlation between density, charring rate and bending resistance, the different methods presented by Eurocode 5 to verify wooden beams under fire exposure were compared, with the use of the software Abaqus/CAE to obtain the isotherms of the beams in the advanced calculation method, and then proposed a new equation to obtain their charring depth according to time of fire exposure. It was confirmed that the density of the wood is inverse to its charring rate and its bending resistance loss, and the advanced calculation method presents less conservative results than the simplified methods. The equation that was proposed in this study had slightly more conservative results than the advanced calculation, proving to be suitable in relation to time spent in calculation, computational effort and economy. DOI:https://doi.org/10.56238/sevened2024.026-028